Case reportSevere intrahepatic cholestasis and liver failure after stanozolol usage – case report and review of the literature - Stępień, Piotr M.; Reczko, Katarzyna; Wieczorek, Anna; Zarębska-Michaluk, Dorota; Pabjan, Paweł; Król, Teodora; Kryczka, Wiesław (Clinical and Experimental Hepatology, 2015)
Stanozolol is a 17α-alkylated synthetic anabolic steroid used illegally by bodybuilders. We present a 19-year-old man who was taking 50 mg of stanozolol intramuscularly, every other day for 2 months, to improve muscle mass. On admission, his bilirubin concentration was 44.34 mg/dl. The serum levels of liver enzymes were normal, with only alanine aminotransferase being slightly elevated. Liver biopsy revealed toxic hepatitis of minor grade with periportal fibrosis and intrahepatic cholestasis. Medical treatment of the patient was conservative. Despite the therapy the patient’s general condition deteriorated – bilirubin level increased to 56.64 mg/dl, and INR rose to 1.7. Then we decided to administer low doses of hydrocortisone. As a result of the treatment, bilirubin concentration was 14.61 mg/dl after 2 weeks. Finally all hepatic enzymes returned to normal values 5 months after stanozolol was discontinued. This treatment appears to be safe and leads to a more rapid reduction of bilirubin.